0116 Autonomic And Sleep Interaction During Acoustic Enhancement Of Sleep. (27th April 2018) - Grimaldi, D; Papalambros, N A; Reid, K J; Abbott, S M; Malkani, R G; Santostasi, G; Sanchez, D J; Paller, K A; Zee, P C
Abstract: Introduction: Acoustic stimulation applied during sleep can enhance slow wave activity (SWA). Given the relationship between sleep and the autonomic nervous system (ANS), we aimed to explore how these two systems interacted in healthy young adults receiving acoustic stimulation. Methods: Twenty subjects (25 ± 4 years, 75% female) participated in a randomized cross-over study with two 2-night visits. After one night of adaptation, participants were randomized to either receive stimulation or sham stimulation on the following night. During NREM sleep, a phase locked auditory stimulation procedure using single input from the midline frontopolar channel, was used to deliver 50ms pulses of pink noise in blocks of 5 (ON intervals) followed by a pause of approximately 6 seconds (OFF intervals). Changes in EEG spectral power across multiple frequency bands were calculated during ON and OFF intervals for both conditions. ANS function was assessed using heart rate variability (HRV) that was quantified before "lights off" over a 5-minute period in supine position and during 5-minute periods of slow wave sleep (SWS) in the first three cycles of sleep. The following HRV measures, representative of cardiac vagal regulation, were calculated: RMSSD (square root of the mean squared differences of successive NN-intervals) and HF% (high frequency, relative power). Results: Acoustic stimulation increased SWA (0.5-4Hz) by 40% and sigma activity (11-15Hz) by 14% during ON vs OFF intervals compared to sham (p<0.01) without changing the overall spectral power across the night. RMSSD before sleep was positively correlated with both SWA (p=0.014, R=0.61) and sigma activity (p=0.006, R=0.60) increase in ON vs OFF intervals during acoustic stimulation. During SWS, HF% was higher in the 2nd and 3rd cycle of sleep during the night of stimulation compared to sham (p=0.02). Conclusion: Higher vagal cardiac modulation before sleep characterized participants who responded to acoustic stimulation with higher SWA and sigma activity enhancement. Sound-induced EEG changes were in turn associated with improved vagal modulation of the heart during SWS. These results suggest the ANS plays a crucial role in the in the brain's response to acoustic stimulation. Support (If Any): DARPA W911NF-16-2-0021.